2021
DOI: 10.1017/s2045796021000159
|View full text |Cite
|
Sign up to set email alerts
|

Use of antipsychotics in Denmark 1997–2018: a nation-wide drug utilisation study with focus on off-label use and associated diagnoses

Abstract: Aims Antipsychotics are primarily labelled for the treatment of severe mental illness and have documented clinical utility in certain neurological disorders or palliative care. However, off-label use of antipsychotics is common and increasing, and prior studies on antipsychotic utilisation have not specifically assessed users in neurology, palliative care or general practice. We aimed to explore diagnoses associated with antipsychotic use, treatment patterns and characteristics of users without diagnoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
0
33
0
1
Order By: Relevance
“…To our knowledge, this is the first study to investigate the cardiometabolic safety of chlorprothixene in its most predominant role today—as anxiolytic or hypnotic used off‐label and at low doses 6,8 . Only one prior study has investigated the cardiovascular safety of chlorprothixene and found similar rates of MACE with use beyond one year 27 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, this is the first study to investigate the cardiometabolic safety of chlorprothixene in its most predominant role today—as anxiolytic or hypnotic used off‐label and at low doses 6,8 . Only one prior study has investigated the cardiovascular safety of chlorprothixene and found similar rates of MACE with use beyond one year 27 .…”
Section: Discussionmentioning
confidence: 94%
“…5 Despite the limited indications, chlorprothixene remains a commonly used antipsychotic in Scandinavia and in a number of other countries 6,7 with evidence of substantial off-label use. 8 Unlike most other first-generation antipsychotics, chlorprothixene has high affinity for 5-HT 2C -, H 1 -and M 3receptors (Table 1). 9 Antagonistic action at these receptors is responsible for some of the anxiolytic and hypnotic properties of chlorprothixene but has also been connected to the development of metabolic disturbances (impaired glucose metabolism or dyslipidaemia).…”
Section: Introductionmentioning
confidence: 99%
“…For example, short-duration treatment of quetiapine in low dosages (i.e., 25-75 mg) is often used to treat insomnia in girls with diagnoses of anxiety disorder, eating disorder, borderline personality disorder, and depressive disorders [16]. A study on prescribing of antipsychotics in primary care in the UK found that low doses of quetiapine are also often prescribed to females diagnosed with anxiety or depression [17] and a recent Danish study reported increased use of low-dose quetiapine outside its approved indications [18]. It is possible that over the years, an increasing number of adolescent girls face unmet medical needs ending in crisis situations where quetiapine use is required.…”
Section: Discussionmentioning
confidence: 99%
“…As weight gain and potential loss are important to many people, it should be shared that little is known about the reversibility of antipsychotic-induced weight gain. This lack of knowledge could affect the decision, especially when drugs are prescribed as off-label ( 3 ), where the potential benefits are less clear. Some may worry that patients with severe mental illness may reject the medication in fear of substantial and irreversible weight gain, and thereby put themselves at risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision making is the cornerstone of modern, evidence-based medicine and requires transparency about risks and benefits associated with any treatment decisions. Second generation antipsychotic medication is the mainstay of treatment of psychotic disorders ( 1 ) and is increasingly prescribed for other indications like bipolar disorder and severe depression and off-label indications such as sleeplessness and anxiety ( 2 , 3 ). Weight gain is a major adverse effect of second-generation antipsychotics, affecting quality of life ( 4 ), personal recovery, and somatic morbidity and is a common reason for antipsychotic discontinuation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%